James Makokis - Fang, Allison; Lynn, Matthew (The Meducator, 2022)
For those who do not watch The Amazing Race on television, Dr. James Makokis may be an unfamiliar name. Besides being the winner of the show’s seventh season, Makokis has established himself as an Indigenous health advocate and gamechanger in transgender patient wellness.